Bloco Eureca - Eu Reconheço o Estatuto da Criança e do Adolescente: referência de educação em direitos humanos e participação social infanto-juvenil - Fernandes, Claudio Oliveira (Universidade Federal de São Carlos, 2023)
The central objective of this thesis is to analyze and understand how the process of education for citizenship and the struggle for the dissemination of human rights for children and young people takes place with and for the collective in the social practice of this group present in the Bloco EURECA’s activity/action (understood here as a continuous educational act of creating, recreating, signifying, and re-signifying). The Bloco EURECA adopts the concept of its own name: EURECA - Eu Reconheço o Estatuto da Criança e do Adolescente, and the group was created in 1991 by the Projeto Meninos e Meninas de Rua/PMMR (Street Boys and Girls Project) in São Bernardo do Campo, in the São Paulo metropolitan area, known as ABCDMRR (which includes the cities: Santo André, São Bernardo do Campo, São Caetano do Sul, Diadema, Mauá, Ribeirão Pires and Rio Grande da Serra). Likewise, the Bloco's proposal brings social criticism in a playful, affectionate, dancing, and joyful way, based on the premise that social rights, as social or sectoral policies, are instruments or mechanisms that support the conception of the human rights "grammar". This research deals with this proposal and presents a reflection on the pedagogical political project, the methodology and the contributions of the activity/action and policies of this Bloco, which naturally perceives, defines, classifies, and positions itself as an insurgent movement around hope and the adoption of a new look and treatment for Brazilian children, especially those in situations of vulnerability, risk, and suffering. The subjects of the research are children, adolescents, young people, social educators, who conceive themselves from the understanding that democracy is constituted where human rights are founding principles in the construction of educational development, considering other grammars and alternative languages to the narrative of the typification of human dignity elaborated in the Global North. EURECA's sambas-enredo (samba songs), produced collectively, bring this dimension to thinking (human rights) and gestures (public policies). The context in which this activity is organized and developed is the result of the demand made by different civil organizations, projects, social movements, and other social sectors located in different geographical areas of the State of São Paulo. The methodology adopted by Bloco EURECA is based on Freirean concepts in dialogue with the theoretical framework of the Epistemologies of the South. This research is a qualitative case study. The case study methodology adopted in this research is in line with participant-action research, given the need to broaden the understanding of the phenomenon studied, which is configured in the experiences of violation lived in the daily lives of the Bloco participants. This crosses the categories of individual, group, social movement, social and political protagonism, allowing changes in the way children are seen and treated, as well as in the elaboration and development of their life projects. Data were collected through observations, field diaries, interviews, and the lyrics of the sambas-enredo (samba songs), which were collectively constructed, to study, in detail, the collective activity/action of Bloco EURECA, which has been going on for more than three decades. The development of the theoretical-methodological process of this work has the same guiding thread present in the activity/action of the EURECA Block: the theoretical-methodological framework of the Epistemologies of the South and Freirianism. The research addressed theoretical-methodological and critical concepts based on themes, such as the Irregular Situation Doctrine; the Integral Protection Doctrine; Estatuto da criança e do adolescente/ECA (Child and Adolescent Statute); Human Rights for Children and Adolescents; Education in and for Human Rights; Social Participation; Citizenship for Children and Young People and Carnival and Samba, considering that the paradigm shift in Brazilian legislation, since 1988, in relation to the construction, assimilation and conception of children, adolescents and young people, is one of the key factors in the creation of EURECA. The results show that the Bloco’s trajectory is based on the principle of social and citizen participation, which dialectically permeates everyday life and the world of ideas. The collective work process resulted in the collective creation and re-creation of more than thirty sambas-enredo (samba songs), in a process of action-reflection-action on the different forms of violation and violence suffered by children and adolescents in Brazilian society and the guarantee of their human rights. The possibility of defining EURECA as an insurgent movement around the adoption of a new way of seeing and treating Brazilian children in situations of vulnerability, risk and suffering is expanded and configured as a way of building political-critical awareness among its participants, starting from the relationship between the intention (the idea of human rights for children and adolescents) and the gesture (the materialization of the right).
Eureca Block - I Recognize the Statute of Children and Adolescents: a reference for education in human rights and social participation of children and youth
Keywords: Estatuto da criança e do adolescente; Bloco EURECA; Direitos humanos infanto-juvenis; Protagonismo infanto-juvenil; Participação social; Child and adolescent statute; EURECA block; Human rights for children and adolescents; Child and youth protagonism; Social participation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; 10. Redução das Desigualdades